Artificial Intelligence as a Driver of Innovation and Sustainability in Digital Business: The Moderating Effect of Financial Management - Sri Maitri, Wayan; Widhya Sedana Putra P, Komang; Lasmi, Ni Wayan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Artificial intelligence has emerged as one of the key drivers of innovation and sustainability in digital businesses. This study explores the impact of AI adoption on innovation and digital business sustainability in Indonesia, along with the moderating role of financial management in this relationship. The research uses Partial Least Squares-Structural Equation Modeling (PLS-SEM) with a purposive sample of owners and managers of digital businesses in Denpasar, Bali. Data were collected through structured questionnaires, then analyzed using SmartPLS 4.0. The findings indicated that AI adoption significantly enhanced innovation and digital business sustainability. Furthermore, financial management had a positive but relatively small moderating effect in enhancing the influence of AI on digital business sustainability. These results also signal that an appropriate AI investment strategy should be supported with relevant financial management in order to maximize all the benefits of AI. This study will be expected to provide a reference for digital business stakeholders, such as SMEs and startups, in the design of sustainable AI adoption strategies.